2015
DOI: 10.1515/euco-2015-0012
|View full text |Cite
|
Sign up to set email alerts
|

Religious Tourism in the South-Moravian and Zlín Regions: Proposal for Three New Pilgrimage Routes

Abstract: This article contains results of the research on religious tourism in the South Moravian and Zlín regions. The aim of this research was to identify new pilgrimage routes. The methodology was based on the implementation of survey interviewers and the design of religious and cultural tourism conceptual strategy. There were 1222 respondents participating in the survey interviewers. The results show that 58% of them consider ‘religious tourism’ a visit to pilgrimage places not just by believers and that 43% of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…The interaction between stakeholders is accounted for from the beginning of development to its ever-continuing management (Hardy 2003;Nowers, De Villiers, Myburgh 2002;Timothy, Boyd 2015). Horák et al (2015) emphasised that the effective integration of all stakeholders, strategic planning, and purposeful implementation of policies and possible activities in developing tourism routes are necessary. For example, Proos, Kath, and Hattingh (2017) found that a lack of support from stakeholders is the main issue in promoting the Maloti Drakensboug Route, and there was a need for support and cooperation among these organisations, which consequently managed to strengthen the image of the destination (Proos, Hattingh 2020).…”
Section: Participation Of Stakeholdersmentioning
confidence: 99%
“…The interaction between stakeholders is accounted for from the beginning of development to its ever-continuing management (Hardy 2003;Nowers, De Villiers, Myburgh 2002;Timothy, Boyd 2015). Horák et al (2015) emphasised that the effective integration of all stakeholders, strategic planning, and purposeful implementation of policies and possible activities in developing tourism routes are necessary. For example, Proos, Kath, and Hattingh (2017) found that a lack of support from stakeholders is the main issue in promoting the Maloti Drakensboug Route, and there was a need for support and cooperation among these organisations, which consequently managed to strengthen the image of the destination (Proos, Hattingh 2020).…”
Section: Participation Of Stakeholdersmentioning
confidence: 99%
“…The Way of St. James has been analyzed both in terms of the conditions of its development, for example by [31], evaluation of facilities and services for pilgrims, for example by [32], or the impact of this pilgrimage route on the development of the territory [30]. This phenomenon has also been addressed in [33,34], who focus on the conditions for building pilgrimage routes in Moravia based on the tradition of Cyril and Methodius.…”
Section: Introductionmentioning
confidence: 99%